Meningkatkan Makna Penelitian Psikologi Melalui Riset Kekinian dan Registri Riset - Abraham, Juneman; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2024)
The relentless development of research in various fields of science, including psychology, has the potential to cause redundancy and reduce relevance. To overcome this, the discourse and efforts of Trend Research and Research Registries were developed. The integration of Trend Research and Research Registry is expected to be implemented and utilized by researchers in the field of science, to not only maintain the quality of research conducted, but to further improve the quality so that it can be more meaningful.